Occupational burn injuries in Finland 2011-2015 - Lotta Purola; Heli Kavola; Jyrki Vuola (BMC, 2022)
Abstract Background This study comprises all hospitalized work-related burn injuries in one country during 2011-2015. The purpose was to describe demographics, causes and risk factors of occupational burn injuries with special focus on the outcome of return to work. Material and methods This is a retrospective study on two data sources of which Finnish Workers' Compensation Center's (FWCC) register includes all work-related burn cases at a given time. Additional data have been obtained from those patients, who were referred to the National Burn Centre (NBC) during the same time according to the Emergency Management of Severe Burns (EMSB) criteria. We compare demographics, injury mechanisms and general burn data of these two patient groups. Results Based on FWCC register, in 2011-2015 occurred 11,623 work-related burn cases of whom 54% were men. During the study period, NBC admitted 26 patients fulfilling EMSB criteria. The most severe patients treated in NBC had injuries affecting multiple body parts. In FWCC data, hand was most injured body part. Kitchen/bakery work was the most common profession in FWCC register but in NBC material industrial and transport professions dominated. In FWCC register, patients had lower mean age (37 years vs. 43 years). Most severe injuries occurred among older patients: In NBC data, those with total body surface area 40% or over had mean age 53 years. Majority of patients returned to work. Conclusion Safety at work in Finland has improved during last decades, and the vast majority of work-related burn injuries are minor. Minor burn injuries are common in young adults working in kitchen and bakery work, whereas elderly men working in transports and industry sustain the most severe burn accidents. Retirement after work-related injury becomes very expensive for all parties, and this data can be used in preventing those cases as well as the minor accidents.